Impact of blockage ratio on the stability of premixed n-butane-air swirl flames - Raj, Vishnu; Prathap, Chockalingam (Physics of fluids (1994), 2024)
This study explores the impact of blockage ratio on the stability of swirl (axial swirl generator with S1.5) stabilized turbulent premixed n-butane/air flames at 1 bar, 300 K, and ϕ = 1.4 and ϕ = 0.8. Particle image velocimetry experiments and delayed detached eddy simulation simulations are employed to reveal the underlying mechanisms. Increasing the blockage ratio leads to (1) a single broader central recirculation zone (CRZ) to an elongated CRZ with a recirculation zone behind the bluff body and (2) higher turbulence and strain levels generated an intense and narrow flame (jet spread rate = 22°–15°). An adverse effect of enhanced strain rate with an increasing blockage ratio narrowed the measured lean blowoff limits ( ϕ = 0.78–0.86). For a higher blockage ratio, the local equivalence ratio ( ϕlocal) to the reaction side decreased due to (1) air entrainment and (2) diffusion of deficient species O2 toward the reaction zone. The entrainment of ambient air into the flame was quantified by estimating root mean square local equivalence ratio ( ϕrms) from predictions, which showed a 12.1% increase at the outer shear layer of the burner having the highest blockage ratio. Furthermore, the Lewis number effect on a low blockage ratio burner revealed preferential diffusion of product species H2O ahead of CO2 toward the preheat zone for Le < 1 condition ( ϕ = 1.4, Le = 0.93). However, based on the local equivalence ratio analysis, no preferential diffusion of the deficient reactant O2 was observed within this regime. The present study with premixed swirl n-butane-air unconfined flames indicated that a higher blockage ratio is beneficial to anchor a stable turbulent flame at ϕ = 1.4, which entrained a large amount of ambient air. In contrast, at lean mixture conditions, the air entrainment decreased the lean blowoff limits at a higher blockage ratio, and hence, a lower blockage ratio is preferable.